Azkadina Catering Marketing Communication Strategy in Attracting Customers - Adnan, A.Evi Elvira (Journal of Entrepreneur, Business and Management, 2024)
One thing that determines the level of business success is how to market products or services to the public. A marketing strategy that uses good communication will certainly gain the trust of customers, the approach taken so that they can maintain loyalty and achieve success in facing any existing competition. The aim of the research is to determine the analysis of Azkadina Catering's marketing communication strategy in attracting customers to choose their catering for various events. The type and source of data used is qualitative data. Sources of informants are catering owners and customers. Data Collection Instruments through Observation, Literature Study, Interviews. Data analysis stage through data reduction, data display and conclusion drawing/verifying and carrying out the SWOT Matrix. The research results show that: 1. Marketing communication in attracting customers at Azkadina Catering results from the IFAS matrix, the strength and weakness factors indicate that internally the implementation of the marketing communication strategy is going well. 2. The results of the strategy provided by Azkadina Catering have won the trust of customers so that they use catering services in a strong condition and are able to compete with catering in the city of Makassar. 3. Based on the results of the EFAS matrix, the opportunity (opportunity) and threat (threat) factors indicate that Azkadina Catering received a good response from customers or service users regarding the communication strategy implemented. Keywords: Marketing Communications, Customers.